Host Interaction and Population Dynamics of Ceratitis capitata in Agroecological Systems: Level Infestation in Key Hosts in Irrigation Oasis of San Juan, Argentina - Rodriguez, Claudia Cecilia; Jofré Barud, Flavia; Gomez, María Pía; Lopez, María Liza (MedWin Publishers, 2024)
This study focuses on the infestation and abundance of Ceratitis capitata (the Mediterranean fruit fly) in various host fruit species in San Juan, Argentina, where agriculture plays a key role in the local economy. The aim of the study was to determine the percentage of infestation and the abundance of pupae in different host species, including peaches, nectarines, plums, apricots, and figs. The results showed significant variation in infestation rates and pupal abundance across the different host species. Peaches, particularly the flat peach variety, showed the highest infestation rates and pupal abundance. Figs also contributed significantly. Infestation levels were highest in the early stages of peach fruit ripening and decreased once peaches were no longer available. Peach varieties, especially flat peaches, were the primary hosts responsible for maintaining C. capitata population. Figs played an important role as well, while plums and apricots were less significant. The findings support the idea that peaches and figs act as a key hosts in this region, similar to results from previous studies, suggesting the importance of these crops in controlling the fruit fly population. Further studies over a longer period could provide deeper insights into the pest's behavior and control strategies.